The Pre-Employment Seminar Activities To Increase Self Esteem In A Social Cognitive Perspective (Case Study On Member Of The Karang Taruna in Muktiwari Village, Cibitung.: - - Novia, Reni (ADPEBI, 2022)
Low growth and a large number of young people who have not worked, from Muktiwari Village, Cibitung Bekasi, make the background of this research, The formulation of this research problem is, How is the pre-employment seminar activity to increase self-esteem in a cognitive social perspective, (study on Members of the Karang Taruna in Muktiwari Village?. The purpose of this study is to determine the activities of pre-employment seminars to increase self-esteem in a social cognitive perspective, (study on Members of the Karang Taruna in Muktiwari Village. The approach used is a qualitative case study, with data collection through in-depth interviews and direct observation of the object of study. This research has a research instrument consisting of 2 key speakers, and 4 supporting sources, which are carried out checking the validity of the data based on the results of observation and trianggulation of sources and data found. One of the results of this study is That parents become the first factor to form self esteem , the participants of pre-employment seminars. The more they are valued by their parents, the more they love themselves and want to change their mindset and behavior to be positive in an effort to work